2015
DOI: 10.1116/1.4919015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying ligand–cell interactions and determination of the surface concentrations of ligands on hydrogel films: The measurement challenge

Abstract: Hydrogels are extensively studied for biomaterials application as they provide water swollen noninteracting matrices in which specific binding motifs and enzyme-sensitive degradation sites can be incorporated to tailor cell adhesion, proliferation, and migration. Hydrogels also serve as excellent basis for surface modification of biomaterials where interfacial characteristics are decisive for implant success or failure. However, the three-dimensional nature of hydrogels makes it hard to distinguish between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…From these studies, it is well known that the surface density of cell adhesion ligands plays an important role in cell adhesion . We have also previously shown the effects of peptide density on the cell adhesion behavior for hydrogel layers on glass substrates and the challenges for quantification of ligand density at the surface of hydrogels, for example, of sP­(EO- stat -PO) films . Assays for the surface-sensitive quantification of cell adhesion ligands on fibrous scaffolds, however, are analytically even more challenging.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these studies, it is well known that the surface density of cell adhesion ligands plays an important role in cell adhesion . We have also previously shown the effects of peptide density on the cell adhesion behavior for hydrogel layers on glass substrates and the challenges for quantification of ligand density at the surface of hydrogels, for example, of sP­(EO- stat -PO) films . Assays for the surface-sensitive quantification of cell adhesion ligands on fibrous scaffolds, however, are analytically even more challenging.…”
Section: Results and Discussionmentioning
confidence: 99%
“…5 We have also previously shown the effects of peptide density on the cell adhesion behavior for hydrogel layers on glass substrates and the challenges for quantification of ligand density at the surface of hydrogels, for example, of sP(EO-stat-PO) films. 31 Assays for the surface-sensitive quantification of cell adhesion ligands on fibrous scaffolds, however, are analytically even more challenging. Yet, this information is important if a comparison between 2D and 3D structures that both bear cell adhesion ligands is envisioned.…”
Section: Resultsmentioning
confidence: 99%
“…Surface analysis techniques, such as Auger electron spectroscopy (AES) and X-ray photoelectron spectroscopy (XPS), can be employed to obtain information on the chemical structure of a surface. 30,31 Besides, it is of interest to note that different quantification methods, including time-of-flight secondary ion mass spectroscopy (ToF-SIMS), radiolabeling, and enzyme linked immunosorbent assay (ELISA), are currently used for the determination of surface ligand concentrations on biomaterials, such as hydrogel systems, 32 providing important data to control or predict biomaterial–cell interaction. Scanning probe techniques, such as scanning electron microscopy and atomic force microscopy (AFM), have also been successfully applied to probe the structure of surfaces, including the measurements of the surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, calibration of principal components analysis (PCA) results from ToF‐SIMS with the C/O ratio obtained by XPS from a plasma‐treated polypropylene samples via partial least square regression showed some promising correlations 28 . Beer et al investigated the performance of XPS, ToF‐SIMS and enzyme‐linked immunosorbent assay (ELISA) for the quantification of amino acid and peptide ligands on a polymer hydrogel film and found that ToF‐SIMS demonstrates higher sensitivity than XPS, allowing the use of ToF‐SIMS to detect peptides at biologically relevant, low quantities that are not accessible by XPS 33 . The polymer system used was an end‐chain functionalised three‐arm polyether that was formed into a hydrogel film, in which the amount of peptide ligand was modulated by varying the relative solution composition of polymer versus ligand.…”
Section: Introductionmentioning
confidence: 99%